Assessment of knowledge and practice regarding menstrual hygiene among adolescent girls in government school of Kanpur Nagar: a descriptive cross-sectional study - Singh, Sapna; Tyagi, Preeti; Anand, Deepak; Gupta, Rashmi (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescent population makes one fifth of world population and in India 21% of the population falls in this group. Social prohibitions and traditional beliefs prevalent in our society lead to inadequate hygiene practices. Methods: Study was done in 304 adolescent girls in a government girls school of Kanpur Nagar by pretested printed questioners in a awareness program on menstrual hygiene. It was a descriptive cross sectional study among 304 school going adolescent girls of 13-19 year age. Results: The mean age of menarche was 13.23 years while mean age of study participants was 15.69 years. Nearly 96.68% used sanitary pads during menses whereas 3.31% use house hold materials. The most common symptom during menstruation was dysmenorrhoea which was recorded in 22.85% study participants. In 79.47% cases first informant was mother about menstruation knowledge while 79.47% girl did not report any social discrimination during menstruation. Conclusions: In this study menstrual hygiene practices among adolescent girls in a government girls school of UP was satisfactory probably because of various government scheme like menstrual hygiene management (MHM), provision of clean water and sanitation facility and distribution of free sanitary pads at monthly interval to all menstruating adolescent girls. Mother was the first informant on menstruation in most cases. Here school teacher can play a pivotal role in educating all adolescent girls and their mother about menstrual hygiene practices.